If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12x + -86 = -8x + -54 Reorder the terms: -86 + -12x = -8x + -54 Reorder the terms: -86 + -12x = -54 + -8x Solving -86 + -12x = -54 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. -86 + -12x + 8x = -54 + -8x + 8x Combine like terms: -12x + 8x = -4x -86 + -4x = -54 + -8x + 8x Combine like terms: -8x + 8x = 0 -86 + -4x = -54 + 0 -86 + -4x = -54 Add '86' to each side of the equation. -86 + 86 + -4x = -54 + 86 Combine like terms: -86 + 86 = 0 0 + -4x = -54 + 86 -4x = -54 + 86 Combine like terms: -54 + 86 = 32 -4x = 32 Divide each side by '-4'. x = -8 Simplifying x = -8
| -2x-11=-x-6 | | X^2-y^2=725 | | 14=2u+8 | | 18x+18=12x+12 | | (3x^2+x-5)(2x-7)= | | -2x+1=-x+2 | | m^2=11m-24 | | 3x-9x+6=20-3+4x | | -15x+19=-8x+12 | | 5x+8y=140 | | 16x-15=10x-9 | | (t-9)(t+36)=0 | | 7x^2+28x= | | 5x=9x-19 | | 10+5(x-2)=-4x+1 | | x(6x-10)=6x^2-60 | | sin^2(x)+cos^2(2x)=1 | | -2y=11+-6x | | 9x-2(3x-10)=23 | | -2y=11-6 | | 2/3x−1/5x=x−1 | | Y=5(15)+b | | -17x-141=-11x-93 | | (b-25)(b+16)=0 | | Y=-.2x+6 | | 16x+208=8x+136 | | 25y^2+110y+121= | | 0(-5/3) | | 0.09xX=59.71 | | -10x+26=-5x+16 | | ln(x+900)=x^2 | | -21x+89=-13x+57 |